2021
DOI: 10.1097/der.0000000000000631
|View full text |Cite
|
Sign up to set email alerts
|

Patch Test Results to European Baseline Series in Turkey: A Prospective and Multicenter Study

Abstract: Background: Patch testing with the European Baseline Series (EBS) is an essential diagnostic tool for the assessment of allergic contact dermatitis.Objective: The aims of the study were to describe the most common contact allergens identified with patch testing in Turkey and to establish the distribution of contact allergens among different regions in Turkey.Patients and Methods: Twelve centers consisting of tertiary health care institutions were included in the study. A total of 1169 patients were patch teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 53 publications
3
11
0
Order By: Relevance
“…Previous studies suggest that PPD should not be considered as a screening agent for textile dye mix contact allergy, and simultaneous reactivity to PPD has been reported in 30%-60% of textile dye mix-positive patients. 12,13 It should also be noted that contact allergy to PPD has shown to be a better indicator of self-reported skin reactions to textiles than textile dye mix. 14 Upon investigating the possibility of cross-elicitation of textile dye mix with PPD, we found that all textile dye reactors were African American and all but one also reacted to PPD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies suggest that PPD should not be considered as a screening agent for textile dye mix contact allergy, and simultaneous reactivity to PPD has been reported in 30%-60% of textile dye mix-positive patients. 12,13 It should also be noted that contact allergy to PPD has shown to be a better indicator of self-reported skin reactions to textiles than textile dye mix. 14 Upon investigating the possibility of cross-elicitation of textile dye mix with PPD, we found that all textile dye reactors were African American and all but one also reacted to PPD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, rates of sensitization to textile dyes have been increasing, and disperse dyes are the most common and most known textile-related contact sensitizer. 13 Differences in rates of sensitization have often been hypothesized to likely rise from exposure patterns, but this question has not been explored. Our study uniquely evaluated this and found personal care products as the overwhelmingly most common source of all positive patch tests in both groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the European baseline series (EBS) is used in all studies conducted in Turkey to report patch test results in patients with ACD. [1][2][3][4][5][6][7][8][9][10] The thin-layer rapid-use epicutaneous (T.R.U.E.) test is a ready-to-use patch test containing 35 allergens.…”
mentioning
confidence: 99%